2017
DOI: 10.3892/mmr.2017.8273
|View full text |Cite
|
Sign up to set email alerts
|

miR‑138 modulates prostate cancer cell invasion and migration via Wnt/β‑catenin pathway

Abstract: The prognosis for prostate cancer patients with distant metastasis is poor, with an average survival rate of 24‑48 months. The exact mechanisms underlying prostate cancer metastasis remain to be elucidated, despite previous research efforts. The present study aimed to reveal the regulatory roles of miR‑138 via Wnt/β‑catenin pathway in prostate cancer cell migration and invasion. Reverse transcription‑quantitative polymerase chain reaction was used to examine the mRNA and protein expression levels and transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…However, in these in vitro scratch assays, we acknowledge that part of the reason we observed lower cell numbers in the scratched area may also be based on the inhibitory effects on cell proliferation. However, there are a number of studies reporting inhibitory effects of miR‐138 on cell migration and invasion in the cancer field, some of which are referenced here . Of these studies, Yu and colleagues recently reported that miR‐138 modulates prostate cancer cell migration and invasion by negatively regulating the Wnt/β‐catenin pathway, a pathway that is also well‐known to be important for osteoblast differentiation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these in vitro scratch assays, we acknowledge that part of the reason we observed lower cell numbers in the scratched area may also be based on the inhibitory effects on cell proliferation. However, there are a number of studies reporting inhibitory effects of miR‐138 on cell migration and invasion in the cancer field, some of which are referenced here . Of these studies, Yu and colleagues recently reported that miR‐138 modulates prostate cancer cell migration and invasion by negatively regulating the Wnt/β‐catenin pathway, a pathway that is also well‐known to be important for osteoblast differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a number of studies reporting inhibitory effects of miR‐138 on cell migration and invasion in the cancer field, some of which are referenced here . Of these studies, Yu and colleagues recently reported that miR‐138 modulates prostate cancer cell migration and invasion by negatively regulating the Wnt/β‐catenin pathway, a pathway that is also well‐known to be important for osteoblast differentiation . Furthermore, cell invasion was found to be inhibited by the ability of miR‐138 to target FAK .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that miRNAs are involved in the regulation of various biological processes such as cancer invasion or migration by targeting the majority of protein-coding genes (11,12). Accumulating data has suggested that the abnormal expression of miRNAs was implicated in the progression of PCa through numerous signaling pathways, including Notch and HIF-1α pathways (13)(14)(15)(16). Hence, it is necessary to determine the functions of miRNAs in PCa, which may reveal a novel mechanism of PCa progression.…”
Section: Terf1 Downregulation Promotes the Migration And Invasion Of mentioning
confidence: 99%
“…miR-1247-5p functions as a tumor suppressor by activating Wnt3 (18). It was also demonstrated that miR-138 modulates prostate cancer cell invasion and migration via the Wnt/β-catenin pathway (19). In the present study, the association of miR-2053 with the PI3K/AKT/mTOR and Wnt/β-catenin pathways in HCC cells was explored.…”
Section: Introductionmentioning
confidence: 84%